Deoxyguanosine kinase. Distinct molecular forms in mitochondria and cytosol - William R. Gower; Michael C. Carr; D.H. Ives (1979)
Two distinct deoxyguanosine kinase activities have been identified in calf thymus tissue. They can be differentiated by subcellular location, electrophoretic mobility, chromatographic behavior, nucleoside specificity, apparent Km values, and end product inhibition. After a 130-fold purification from mitochondrial extract, the newly discovered kinase was specific primarily for deoxyguanosine and deoxyinosine. Unlike the cytosol enzyme, which proved to be the broadly specific deoxycytidine kinase studied previously, the mitochondrial enzyme does not phosphorylate deoxycytidine. Its apparent Km for deoxyguanosine, 6 micromolar, is 2 orders of magnitude lower than that of the cytosol enzyme. The mitochondrial enzyme is strongly inhibited by dGTP and dITP and activated up to 6-fold by dTDP and UDP, whereas neither dCTP nor dATP had much effect.